STUDENTS' LEARNING OBSTACLES IN SOCIAL ARITHMETIC - Nisa Azzahra; Tatang Herman (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
Social arithmetic is one of the essential subjects for 7th-grade students because it is related to everyday life. However, the facts show that many students still have learning problems about the application of social arithmetic. The obstacle experienced by students is due to the students' obstacle in learning social arithmetic. This study aimed to obtain previous research on junior high school students' learning obstacles on social arithmetic. This study method is a systematic literature review (SLR), a descriptive-based survey in the form of an analysis of 23 articles from the Google Scholar database, with the keywords learning obstacle, analysis error, and difficulties in social arithmetic. The results showed that three types of learning obstacles, namely didactical obstacles, ontogenic obstacles, and epistemological obstacles. In addition, obstacles occur in concepts (profit, loss, discount), procedures (modeling and concluding), operational techniques (multiplication of percentage and division), and textbooks used because of the language that is difficult to understand and does not fit the context recognized by students. The research implies providing information on the obstacles experienced by students and research gaps from the results of this review for future research, namely research on analyzing textbooks.